Forms of rejection in kidney transplantation - Larre Borges, Uruguay; Sanguinetti, Julio; Servetti, Eduardo; Gastambide, Gustavo (Cirugía del Uruguay, 1972)
Hyperacute and chronic rejections in cases of kidney transplants are discussed ·n general. There are two distinct anatomopathological pictures in hyperacute rejections, though both respond to the same clinical type. Chronic rejection takes on a characteristic forro.